Rancang Bangun Infrastruktur IP-PBX Trixbox Berbasis Virtual Machine Di Universitas Ibrahimy - Keliana Khamisah; Abdus Somad; Elfina Eldiavani; Manda Nuria Suhailatin Najwa; Mamluatur Rizkiyatul Nafiah (LKP KARYA PRIMA KURSUS, 2026)
This study designs and implements a voice communication infrastructure based on Internet Protocol Private Branch Exchange (IP-PBX) using Trixbox in a Virtual Machine environment at Universitas Ibrahimy. The problem addressed is the need for efficient, manageable, and stable internal communication without increasing physical device requirements. The research method includes needs analysis, network topology design, virtual server installation, SIP extension configuration, and quality testing using Quality of Service (QoS) parameters. The implementation results show that Trixbox runs stably on a virtual server and supports effective communication among clients. QoS testing produced an average latency of 18.4 ms, jitter of 2.3 ms, packet loss of 0%, Mean Opinion Score (MOS) of 4.2, and a call setup time of 0.6 seconds. These values indicate that the system is in a very good category and is feasible as an internal campus communication solution. Keywords: VoIP, Trixbox, IP-PBX, Virtual Machine, QoS, Universitas Ibrahimy.